Anti-inflammatory activity of methanolic extract of Ficus hispida dried fruit - Choudhury, Asif; Jha, Deepak Kumar; Rajashekhar, U. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Natural products are a valuable resource of novel bioactive metabolites and these products exist in which the anti-inflammatory activity. The present investigation studies the in vivo and in vitro anti-inflammatory activity of methanolic extract of Ficus hispida in rat’s model. Methods: Plant material was extracted with methanol in a Soxhlet extraction apparatus. Indomethacin was used as a standard drug here, which is a known potent inhibitor of PG synthesis. The carrageenin and histamine induced paw oedema were selected to represent models of acute inflammations. The test compounds and standard drugs were administered orally. After 60 minutes paw oedema was induced by giving 0.1 ml of 1% Carrageenan and 0.1 % histamine by sub-plantar administration. Paw volume-Plethysmometer by mercury displacement method, before and after 1 hr to 4 hours of carrageenan and histamine administration. Performed MTT-based cytotoxicity assay of the Ficus hispida on the RAW264.7 cell line to determine the IC50 and calculate the pro-inflammatory cytokines viz, IL-6, IL-1β and TNF-α and compared to the LPS control. Results: The result obtained from the in-vivo study shows that the Ficus hispida has significant anti- inflammatory activity in a dose dependent manner. This effect is similar to that produced by NSAIDS such as Indomethacin. The concentrations of IL-6, IL-1β and TNF-α, secreted by the cells after challenging with bacterial LPS (2 µg/ml) and subsequent treatment with 50 µg Ficus hispida has been found to reduce the production of all the three pro-inflammatory cytokines viz, IL-6, IL-1β and TNF-α as compared to the LPS control. The activity, in fact, is comparable to the standard NSAID Indomethacin. Conclusions: All these findings and phytoconstituents present in the extract could be the possible chemicals involved in the prevention of inflammations.